Automated and verified deep learning - Behl, HS (2021)
In the last decade, deep learning has enabled remarkable progress in various fields such as image recognition, machine translation, and speech recognition. We are also witnessing an explosion in the range of applications. However, there are many challenges that stand in the way of the widespread deployment of deep learning. In this thesis, we focus on two of the key challenges, namely, neural network verification and automated machine learning.